Thermodynamic and Kinetic Analysis of a CO2 Hydrogenation Pilot Scale Reactor for Efficient Methanol Production - Antonis Peppas; Chrysa Politi; Konstantinos Charalampopoulos; Vasiliki Kontou; Sotirios Karellas (Eng)
Decarbonization of hard-to-abate industrial sectors, namely the extractive industries, has become an imperative, and thus, processes such as carbon capture and utilization (CCU) have been explored thoroughly and seem to be a promising solution. Carbon dioxide (CO2) catalytic hydrogenation employing green hydrogen (H2) to produce synthetic methanol (MeOH) aims to utilize industrial-captured carbon. A thermodynamic and kinetic analysis of a pilot scale methanol synthesis reactor was conducted by modeling the process using Aspen Plus V12 software. The methanol synthesis model consists mainly of a multi-tubular packed-bed reactor with a thermal oil heat recovery system, a product separator, and an internal recycle loop for optimal efficiency. The reactor has a 5 kg h−1 methanol production capacity, and its heat recovery system achieves an overall heat reduction of 64.1% and can retrieve 1.293 kWh per kg of methanol produced. The overall carbon conversion achieved is 80.6%. Valuable information concerning the design and profile of the reactor is provided in this study.